Determining and mapping land suitability for porang (Amorphophallus oncophyllus L.) cultivation in Madiun Regency, Indonesia - Dheka Agustin Prasetyowati; Siswanto; Kemal Wijaya (Jurnal Ilmiah Pertanian, 2023)
The porang plant is a tuber plant. Porang tubers currently have an economical selling value. Due to the economic value of porang, several regions in Indonesia now cultivate it. Therefore, land suitability analysis is needed to determine whether or not porang or other commodities can be planted in an area. This study aimed was determining the actual and potential land suitability classes on porang land and the constraints that may occur, also mapping the land suitability of porang in three villages of Kare District, Madiun Regency, Indonesia, i.e., Kuwiran, Randualas, and Kare, using a system geographic information (GIS). This study used survey and matching methods while making maps using ArcGIS 10.4 software. Primary and secondary data were obtained from laboratory analysis results, field observation, and related data from the Meteorology, Climatology, and Geophysics Agency (BMKG). The results showed that Kare Village had good potential for porang cultivation based on the results of spatial data processing. The actual land condition for porang cultivation in Kuwiran Village was 10 ha, Randualas Village was 28 ha, and Kare Village was 18.55 ha. The limiting factors at the study site were nutrient retention and availability. Some efforts can be made to improve the land by applying organic matter, compost, and liming.